Implementation of Corporate Governance (Case Study of Insurance Companies in Indonesia) - Lucky Nugroho; Minanari; Safira; Anees Janee Ali; Audita Setiawan; Yananto Mihadi Putra (IAEI, 2023)
The occurrence of bankruptcy in insurance companies in Indonesia shows indications of weak mitigation and not optimal implementation of corporate governance. Therefore, this conceptual paper aims to discover the types of risks in companies and the types of risks in insurance companies. The method used is qualitative. The method used is descriptive qualitative, which aims to explain certain phenomena or events in depth without measuring variables with numbers or statistics. In this conceptual paper on insurance company risk, qualitative methods aim to identify existing risks and provide views on good governance practices to deal with them. The result of this conceptual paper is that risk management is one step in mitigating companies from losses and bankruptcy, and insurance companies in Indonesia must be able to manage existing risks and apply good governance to maintain business sustainability. The implications of this conceptual paper provide information and references as well as new scientific treasures related to implementing risk management and the types of risks found in insurance companies.